Research on the variation in the Shields curve of silt initiation - Qi Qinghui; Dong Peihua; Qu Hongling (Open Geosciences)
The sediment particles on muddy coasts are relatively fine, and they are easy to move under the dynamic action of wave power, which can easily cause sedimentation problems in port channels. Therefore, the problem of silt initiation is a key issue for in-depth research in the development process of silt coast harbors. Based on a large amount of experimental data on silt initiation in silty coast conducted by predecessors, the relationship between the incipient Shields number and sediment parameters such as sediment particle size and sediment density was quantitatively analyzed. The explicit calculation formula of the incipient Shields number is established, and the modified distribution map of the incipient curve zone is drawn. The role of particle size and sediment density in sediment incipient motion was elucidated. The modified distribution map of the incipient motion curve was drawn, which promotes the application of the Shields curve in muddy coastal engineering.